Penerapan Model Group Investigation (GI) dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam: Implementation of the Group Investigation (GI) Model to Enhance Islamic Religious Education Learning Outcomes - Hafizia Haryanto, Friska; Aliyah, Adah; Rosadi, Adi; Marwiji, Muh. Hasan (Risalah Kharisma, 2024)
This study examines the low learning outcomes in Islamic Education (PAI) among 11th-grade Science 1 students at SMA Negeri 1 Cidahu, caused by conventional, non-interactive teaching methods that reduce motivation and engagement. Many students fail to meet the Minimum Competency Standards (KKM) due to passive learning. To address this, the research evaluates the effectiveness of the Group Investigation (GI) cooperative learning model in improving student participation and understanding, particularly on the topic "Spirit of Worship by Believing in the Day of Judgment." Using Classroom Action Research (CAR) over two cycles with 36 students, data was collected through observations, tests, interviews, and documentation, then analyzed descriptively and statistically. Results show that GI significantly boosts active participation and comprehension, with a marked increase in students achieving KKM. The study concludes that GI is an effective alternative for enhancing PAI learning quality, promoting engagement, and improving outcomes at the secondary level.